Analisis Kemampuan Motorik Halus Anak Melalui Kegiatan Kolase di RA Darussalam Kota Siantar - Nur Hamni Lubis; Annisa Wahyuni; Ali Masran Daulay (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
This research is titled "Analysis of Children's Fine Motor Skills Through Collage Activities at RA Darussalam, Siantar City." The study aims to assess children's fine motor skills through collage activities and identify supporting and inhibiting factors. A qualitative approach with descriptive analysis was employed. The findings indicate that collage activities significantly enhance children's fine motor skills, including cutting, gluing, and arranging materials. Children demonstrated progress in fine motor skills after several sessions, with variations in development depending on the guidance received. Key supporting factors include the availability of diverse materials and active educator guidance, while challenges faced include time constraints and individual difficulties. This research is expected to provide guidance for educators in designing activities that support the development of fine motor skills in early childhood.